Soybean Dregs as Main Ingrediens of Pollen Substitute for Apis Cerana Honey Bees - Retno Widowati, Harini Nurcahya Mariandayani, Indra Lesmana Rahayu, Wellyzar Sjamsuridzal, Adi Basukriadi, Ariyanti Oetari (International Journal of Modern Agriculture, 2020)
The first objective of this research was to used soybean dregs as pollen substitute. The second objective was test the preferences, preventing abscond and productivity of Apis cerana honey bees colonies consumed the pollen substitute. There were two types of pollen substitute flour (PS) and four types of pollen substitute pasta given to A. cerana honey bee colonies at apiary in Bandung, West Java, Indonesia. The basic ingredients of PS1 flour were soybean dregs, skim milk and instant baker’s yeast. The basic ingredients of PS2 flour were soybean dregs, skim milk and tapai (a Indonesia traditional fermented food) starter. The PS1-A paste consisted of PS1 and sugar syrup; PS1-B contained of PS1 and molasses; PS2-A contained of PS2 and sugar syrup; and PS2-B contained of PS2 and molasses. The nutrition of each type of pollen substitute was analyzed. Each type of PS paste was given to five honey bee colonies for five weeks. The best pasta was given to the five honey bee colonies for 15 weeks in dearth periode. The best pasta was given to three colonies for 7 weeks also to test the productivity. The control colonies were not given PS. All of the colonies forage naturally. The analysis of nutrition showed that protein and other nutrients in PS1-A pasta were better than other PS. Honey bee colonies consumed more PS1-A than any other PS. The giving of PS1-A pasta for 15 weeks was able to maintain 5 colonies and they were not abscond. The colonies given PS1-A showed an increase the weight of honey and the volume of honey compared to the control colonies. Honey produced was in accordance with Indonesian National Standard for honey (SNI-01-3545-2004). The conclusion of this research were soybean dregs could be main indegrients of pollen substitute, the PSA-1 was able to prevent abscond and increased productivity of A. cerana colonies.